PAPAYA LEAF EXTRACT BENEFITS IN THE SYMPTOMS OF DENGUE - Shiri., Pro. Himashi (International Journal of Multidisciplinary Research and Studies, 2021)
The Carica papaya splint is acquiring the interest as an implicit remedial element for taking the edge off dengue-and non-dengue-accompanying thrombo-cytopaenia. In that estimate, safety examinations are as important as efficacy eventuality. The safety appraisal of botanical products for mortal use is tricky by shifting phrasings, legion phytochemical conformation, and foreign manures. This examination aimed to totally organize connected safety clinical and preclinical data, as well as reports on condiment- medicine relations of C. papaya splint consumption. Styles. A methodical hunt using pre-planned keywords on electronic databases (MEDLINE, Cochrane Library Central, LILACS, and Web of Science) and slate literature was conducted. Applicable clinical and preclinical studies were linked, screened, and anatomized to present an overall safety profile of papaya splint consumption. Results. An aggregate of 41 papers was included (23 clinical, 5 ongoing trials, and 13 preclinical) for descriptive analysis on study characteristics, adverse responses, toxin findings, and condiment-medicine relations, from which 13 randomized controlled and quasi-experimental trials were further assessed for the threat of bias and reporting quality. Overall, C. papaya splint consumption (in the form of juice and formalized waterless excerpt) was well permitted by adult humans for short durations (5 days).[1]